g(x) = - log(x) + 2

Description of transformation:

Equation(s) for the vertical asymptote(s):

x-intercept in (x,y) form:

The line does not cross over the x-axis so I'm lost with this problem; need help.

g(x) = - log(x) + 2

Description of transformation:

Equation(s) for the vertical asymptote(s):

x-intercept in (x,y) form:

The line does not cross over the x-axis so I'm lost with this problem; need help.

Tutors, please sign in to answer this question.

1) Flip f(x) = g(x) about x-axis to get y1 = -log(x). Move y1 = -log(x) up by 2 units to get g(x) = - log(x) + 2.

2) x = 0, since when x-->0, y-->-oo.

3) x-intercept is at (100, 0), since -log(100) + 2 = 0, if the base is 10.